2‐Methoxy‐4‐methylsulfinylbenzyl: A Backbone Amide Safety‐Catch Protecting Group for the Synthesis and Purification of Difficult Peptide Sequences. Issue 46 (3rd October 2014) - Paradís‐Bas, Marta; Tulla‐Puche, Judit; Albericio, Fernando
Abstract The use of 2‐methoxy‐4‐methylsulfinylbenzyl (Mmsb) as a new backbone amide‐protecting group that acts as a safety‐catch structure is proposed. Mmsb, which is stable during the elongation of the sequence and trifluoroacetic acid‐mediated cleavage from the resin, improves the synthetic process as well as the properties of the quasi‐unprotected peptide. Mmsb offers the possibility of purifying and characterizing complex peptide sequences, and renders the target peptide after NH4I/TFA treatment and subsequent ether precipitation to remove the cleaved Mmsb moiety. First, the "difficult peptide" sequence H‐(Ala)10‐NH2 was selected as a model to optimize the new protecting group strategy. Second, the complex, bioactive Ac‐(RADA)4‐NH2 sequence was chosen to validate this methodology. The improvements in solid‐phase peptide synthesis combined with the enhanced solubility of the quasi‐unprotected peptides, as compared with standard sequences, made it possible to obtain purified Ac‐(RADA)4‐NH2. To extend the scope of the approach, the challenging Aβ(1‐42) peptide was synthesized and purified in a similar manner. The proposed Mmsb strategy opens up the possibility of synthesizing other challenging small proteins.